Maps for the getaway : a novel - Noblin, Annie England (William Morrow, 2021)
When they posed for a photo at their high school graduation, they vowed they'd be friends forever, but teenage promises are so easily broken, and now, thirty years later, they're practically strangers. Cici, stuck in a rut, married to a cheating husband. Genie, caring for her ailing father but never getting any thanks. Kate, everyone knows people who look perfect on Instagram are not. And Laurie, the most successful of them all, now tragically gone. So, to celebrate Laurie's life, three former friends in a 1962 red Lincoln Continental convertible take the road trip of their lives, encountering male strippers, a boy band that has seen better days, crazy motel rooms, adopting a so-ugly-it's-cute stray dog, and discovering that it's never too late to live the wild life.